ARTIFICIAL INTELLIGENCE USAGE IN HIGHER EDUCATION: EFL STUDENTS’ VIEW - Yuliani, Sesilia; Mukhibbah, Tefanya Laili; Agustina, Eliasanti (ELTR Journal, 2024)
This research aims to determine students' perceptions and challenges faced using AI due to the gaps faced by EFL students. This research uses a qualitative method which uses two data collection techniques, namely observation as supporting data and interviews with 6 students from different classes as main data. To analyze the data, researchers used thematic analysis and then used content validity to support the research. The results of this research show that the majority of students agree that the use of AI in EFL classes is very helpful in the independent learning process and improves speaking, reading, writing, and giving ideas. So the researchers concluded that based on students' perceptions, these perceptions had a positive impact on the use of AI in EFL classes. Researchers hope that students and lecturers can use AI according to the role of AI. Researchers also hope that this research can become a reference for readers.